Efficacy of ADDIE Instructional Design in Promoting Conceptual Change in Electronic Concepts at Tano-North Municipality, Ghana - Amankwaah, Daniel; Appiah-Twumasi, Eric; Ateko, Kenneth Darko; Asamoah, Yao Donusem (Schrödinger: Journal of Physics Education, 2024)
Purpose of the study: This study sought to determine the efficacy of the ADDIE instructional design in facilitating the conceptual change of senior high school physics students in Tano-North Municipality in Electronics. Methodology: A design-based research (DBR) methodology was adopted using a sample of 101 participants. Data were collected using a 10-item Electronic Concepts Test (ECT). Data were analyzed quantitatively (frequencies, percentages, and Wilcoxon Signed Rank Test) and qualitatively (content analysis). Main Findings: The results revealed that significantly high percentages of students (71.29% to 94.06%) demonstrated misconceptions about electronics concepts. The content analysis of the students' responses revealed various misconceptions, including 'temperature increases conductivity of the conductors' and 'heat increases conductor temperature,' among others. However, there was a significant increase in the percentage of students exhibiting scientific understanding after the intervention (Z = -2.83, p = 0.002, with a large effect size of r = 0.89). Novelty/Originality of this study: While much attention has not been turned to the use of ADDIE instructional design as an instructional approach in physics teaching or, for that matter, the study of electronics, this study has revealed the efficacy of the ADDIE instructional design in promoting students' conceptual change in electronics concepts in the Tano-North Municipality. Based on the results, the researchers recommended the ADDIE instructional design to high school physics teachers in the Tano-North Municipality for teaching and learning electronics concepts.